Gambaran Minat Dan Pengetahuan Guru Terhadap Program UKGS Di SDIT Fithrah Insani 2 Kabupaten Bandung - Putri, Anggit Nastiti; Nurnaningsih, Hera; Octaviana, Devy; Nurjanah, Neneng (Jurnal Terapi Gigi dan Mulut, 2024)
UKGS is a program that aims to improve the level of dental and oral health of school students. Teacher interest and knowledge are factors in the existence of the UKGS program in schools because interest is preceded by knowledge of the intended object, while interest is a desire accompanied by an action. The purpose of this study was to determine the description of teachers' interest and knowledge of the UKGS program. This descriptive study involved a population of 35 teachers, with the sample selected through total sampling. Data collection was conducted by distributing questionnaires. The results indicate that 82.9% of respondents have a very high level of interest in the UKGS program, and 17.1% have a high level of interest. In terms of knowledge about the UKGS program, 65.7% of teachers fall into the good category, 20% into the moderate category, and 14.3% into the low category. The data indicate that most teachers have high interest and good knowledge of the UKGS program. This is attributed to the teachers' strong desire and awareness to improve students' dental and oral health, the ease of accessing various information resources, and their work experience.